A Greek Translation of the Brunel Mood Scale: Initial Validation among Exercise Participants and Inactive Adults - Symeon P. Vlachopoulos; Andrew M. Lane; Peter C. Terry (MDPI AG, 2023)
The aim of the present study was to provide initial validity evidence of a Greek translation of the 24-item Brunel Mood Scale, referred to as the BRUMS-Greek, a measure of anger, confusion, depression, fatigue, tension, and vigour. Data were collected from 1417 Greek adult exercise participants and 369 physically inactive adults, totaling 1786 adults (male = 578, female = 1208) aged 18-64 years (M = 34.73 ± 11.81 years). Given the large univariate and multivariate non-normality, a confirmatory factor analyses treating responses as ordered categorical variables was conducted which supported the hypothesised six-correlated factor measurement model. The internal consistency reliability of the BRUMS-Greek subscales was supported via Cronbach alpha coefficients. The construct validity of the scales was supported (a) via correlations in the hypothesised direction with trait positive and negative affect, (b) with more positive and less negative moods reported immediately after participation in a single exercise class compared to pre-exercise mood, and (c) with exercise participants reporting more positive and less negative mood states compared to physically inactive adults. Women reported higher tension and lower vigour scores than men. Tension scores were higher and confusion scores lower among younger participants (≤35 years) than older participants (≥36 years). Participants with obesity reported higher negative mood scores than those who were underweight or normal weight. In sum, the BRUMS-Greek demonstrated acceptable psychometric characteristics, and is proposed to be a suitable measure for use with exercise participants, physically inactive adults, and other Greek populations to explore research questions related to mood.